2023
DOI: 10.1002/slct.202204153
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate‐Assisted Remediation of Pb(II) From Jarosite

Abstract: Jarosite is an essential solid industrial waste material which is generated during the hydrometallurgical processing of zinc in smelters. Besides zinc and iron, Jarosite also contains toxic heavy metals like Pb, Cd, Al, Cr, Cu etc. due to which it is environmentally hazardous. Due to the presence of heavy metals, the useful Zn, Fe components cannot be utilized safely. Therefore, it is necessary to remove Pb(II), a major toxic element, to make it useful. In this report, a green process for immobilization of Pb(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…This is probably because the polar solvents stabilize the first excited state of the molecules better than their ground state. 49,50 THF is a similar polar solvent to chloroform. It is reported that in THF, the packing order of the aggregates of small molecules maximizes due to the dipole-dipole interaction between the oligoethers and THF molecules.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably because the polar solvents stabilize the first excited state of the molecules better than their ground state. 49,50 THF is a similar polar solvent to chloroform. It is reported that in THF, the packing order of the aggregates of small molecules maximizes due to the dipole-dipole interaction between the oligoethers and THF molecules.…”
Section: Resultsmentioning
confidence: 99%
“…N‐alkyl‐3‐formylphenothiazine under reflux/ultrasonic compound is synthesized in the laboratory, their result has been found as antitumor activities [154] . Singh obtained aromatic compounds from waste polystyrene, polyethylene, polypropylene plastics, which can be used in the medicinal field [155–160] . Pagadala et al synthesized various heterocyclic compounds containing nitrogen, oxygen, and sulfur heteroatoms in a water solvent [161] .…”
Section: Benzopyran Derivatives Nomenclaturementioning
confidence: 99%
“…The SWNTs are synthesized from virgin LD-PE and PP plastics. [105] LD-PE and PP are pyrolyzed at between 370 to 550 °C ranges, [105][106][107][108][109][110][111][112][113][114][115] which is determined by TGA. The high quality of the SWNTs was found with an oxidation peak at 588 °C while the oxidation of graphite flakes that a shoulder peak between 400 to 500 °C, which encapsulates the MgO supported by a catalyst-free approach during the CVD process.…”
Section: Analyzed Cnts Materialsmentioning
confidence: 99%